Delayed diagnosis of Gorlin–Goltz syndrome: The importance of the multidisciplinary approach - Figueira, Jéssica Araújo [UNESP]; de Souza Batista, Fábio Roberto [UNESP]; Rosso, Karina; Veltrini, Vanessa Cristina; Pavan, Angelo José (Wolters Kluwer, 2018)
Gorlin–Goltz syndrome (GGS), also known as nevoid basal cell carcinoma syndrome, is an autosomal dominant inherited disorder with high penetrance and variable expressivity. The classic triad originally described by Gorlin and Goltz in 1960 is composed of multiple nevoid basal cell carcinomas (NBCCs), odontogenic keratocysts (OKCs) in the jaws and bifid ribs. in 1977, this triad was modified by Rayner et al, and to GGS diagnosis, the OKCs had to appear in combination with calcification of the cerebellar falx or palmar and plantar pits. It may occur that although GGS syndrome is a well-known condition, only the specific symptom could be observed by different specialists. Therefore, the patient cannot be placed in an always complex clinical panel. The authors introduce an example in this report. In the present case, the patient had NBCCs, OKCs, and probably other signs of GGS since 1998, and has been treated for this conditions separated, without a diagnosis of a syndromic condition. A 54-year-old white woman was referred to the oral medicine service due to cyst located in the right mandibular body. She had history of skin cancer and undergone surgeries and radiotherapies for the lesions treatment, scars on the skin face due to the lesions removed, and a new ulcerated lesion on the back of was diagnosed. In addition, the patient presented frontal and parietal bossing leading to increased cranial circumference, hypertelorism, strabismus, broad base, and mandibular prognathism. To the image 9w?>examination, skull radiography revealed calcification of the falx cerebri; on chest X-ray bifid rib was observed and spine radiography showed vertebral osteophytes. Panoramic radiograph showed a well-defined bilocular radiolucent image located in posterior and anterior mandibular region. The whole elements induced us to investigate the patient’s past medical history, which revealed that since 1998 had the diagnosis of NBCC and OKC. A multidisciplinary approach becomes necessary for the diagnosis and follow-up of patients with GGS, considering the complexity of the clinical manifestations. Therefore, it is of primary importance for dental surgeons and dermatologists to know the signs and symptoms of GGS to perform early diagnosis and to avoid progression of the oral cysts or metastasis of the skin lesions.
Keywords: Gorlin–Goltz syndrome; Jaw; Keratocyst